Weakening of Coastlines and Coastal Erosion in the Gulf of Guinea: The Case of the Kribi Coast in Cameroon - Philippes Mbevo Fendoung; Mesmin Tchindjang; Aurélia Hubert-Ferrari (Land, 2022)
For more than four decades, the Gulf of Guinea’s coasts have been undergoing a significant phenomenon of erosion, resulting from the pressures of both anthropogenic and marine weather forcings. From the coasts of West Africa (Senegal, Ivory Coast, Ghana, Benin, Togo, and Nigeria) to those of Central Africa (Gabon, Equatorial Guinea, and Cameroon), the phenomenon has been growing for more than four decades. The southern Cameroonian coastline from Kribi to Campo has become the scene of significant environmental dynamics that render it vulnerable to coastal erosion, which appears to be the major hazard of this coastal territory and causes a gradual degradation of the vegetative cover, thereby leading to the degradation of the coast’s land/ground cover and human-made infrastructure. The objective of this work is to analyze the kinematics of the Kribian coastline between 1973 and 2020; to quantify the levels of retreat, accretion, and stability; and finally, to discuss the factors influencing the evolution of the coastline. The methodological approach is based on the large-scale processing of Landsat images with a spatial resolution of 30 m. Then, small-scale processing is carried out around the autonomous port of Kribi using Pléiades and Google Earth images from the years 2013, 2018, and 2020 with a 0.5 m spatial resolution. The Digital Shoreline Analysis System (DSAS) version 5 and ArcMap 10.5® tool are used to model coastal kinematics. In addition, the dynamics of the agro-industrial plantations are assessed via satellite images and landscape perception. Environmental degradation is measured with respect to the entire Cameroonian coastline through the supervised classification of Landsat images (1986–2020). The results show that erosion is in its initial phase in Kribi because significant retreats of the coastline are noticeable over the period from 2015–2020. Thus, between 1973 and 2020, the linear data present a certain stability. In total, +72.32% of the line remained stable, with values of +1.3% for accretion and +26.33% for erosion—obtained from Landsat images of 30 m resolution—with an average retreat of +1.3 m/year and an average accretion of 0.9 m/year between 1973–2020. Based on high-resolution images, between 2013 and 2019, the average retreat of the coastline on the Kribian coast was −8.5 m/year and the average accretion was about 7 m/year. Agro-industrial plantations are responsible for environmental degradation. Thus, at SOCAPALM in Apouh, there has been a clear growth in plantations, which has fallen from 53% in 1990 to 78% in 2020, i.e., an increase of 25% of its baseline area. This is linked to the fact that plantations are growing significantly, with increases of 16% in 1990, 28% in 2000, and 29% in 2020, for old plantations.